Resting Stages of Skeletonema marinoi Assimilate Nitrogen From the Ambient Environment Under Dark, Anoxic Conditions. Issue 3 (29th February 2020) - Stenow, Rickard; Olofsson, Malin; Robertson, Elizabeth K.; Kourtchenko, Olga; Whitehouse, Martin J.; Ploug, Helle; Godhe, Anna
Abstract : The planktonic marine diatom Skeletonema marinoi forms resting stages, which can survive for decades buried in aphotic, anoxic sediments and resume growth when re‐exposed to light, oxygen, and nutrients. The mechanisms by which they maintain cell viability during dormancy are poorly known. Here, we investigated cell‐specific nitrogen (N) and carbon (C) assimilation and survival rate in resting stages of three S. marinoi strains. Resting stages were incubated with stable isotopes of dissolved inorganic N (DIN), in the form of 15 N‐ammonium (NH4 + ) or ‐nitrate (NO3 − ) and dissolved inorganic C (DIC) as 13 C‐bicarbonate (HCO3 − ) under dark and anoxic conditions for 2 months. Particulate C and N concentration remained close to the Redfield ratio (6.6) during the experiment, indicating viable diatoms. However, survival varied between <0.1% and 47.6% among the three different S. marinoi strains, and overall survival was higher when NO3 − was available. One strain did not survive in the NH4 + treatment. Using secondary ion mass spectrometry (SIMS), we quantified assimilation of labeled DIC and DIN from the ambient environment within the resting stages. Dark fixation of DIC was insignificant across all strains. Significant assimilation of 15 N‐NO3 − and 15 N‐NH4 + occurred in all S. marinoi strains at rates that would double the nitrogenous biomass over 77–380 years depending on strain and treatment. Hence, resting stages of S. marinoi assimilate N from the ambient environment at slow rates during darkness and anoxia. This activity may explain their well‐documented long survival and swift resumption of vegetative growth after dormancy in dark and anoxic sediments.